Collaborative Research and Development Projects A Practical Guide - Harris, Tom. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
A lot of time and money is invested in collaborative research and development projects at universities, research institutes and companies. But how should these complex projects be planned and run to create valuable commercial outcomes? This book is a manual for all individuals and organisations from academia and industry working together on research and development projects. Whether grant funded, company to company or academic to company, this inspiring and highly readable book covers winning grant support, the legal arrangements, working with academics and practitioners, managing project progress and exploiting the project results. The examples, practical methods and tips in this book will not only help the reader prepare for grant applications, but more importantly help to achieve the best results and returns from every collaborative project.